Exposure to TV news in Iraq and its relationship to press and radio news D- A field study to determine a probabilistic indicator of changes in exposure to news over two years. (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, and prayers and peace be upon Muhammad and his God, the good and the pure.Public exposure to the media, especially radio and television, is of particular importance.Because of the importance of this function for both parties, the audience and the medium only, but also because the news works onCreate perceptions that are accepted - to some extent - by the public, which often lacks a mechanism of confirmation.A natural facilitator, first and second, creating an unlimited relationship between the mediaaudience, contents of the news (the event’s cause), its characters, its source, and its possible subsequent development)The three elements that were mentioned are (the subject of our research, because we do not study here the details of the publicfor news), but how does the public see and care about the contents of the news? And it's an early subjectAccording to the modest researcher's research. We also investigated the difference between exposure toOver two years, this disparity was affected by the nature of each communication method separately.